2019
DOI: 10.1002/ijc.32793
|View full text |Cite
|
Sign up to set email alerts
|

Decreased local immune response and retained HPV gene expression during chemoradiotherapy are associated with treatment resistance and death from cervical cancer

Abstract: More than one-third of patients with locally advanced cervical cancer do not respond to chemoradiation therapy (CRT). We aimed to characterize the transcriptional landscape of paired human cervical tumors before and during CRT in order to gain insight into the evolution of treatment response and to elucidate mechanisms of treatment resistance. We prospectively collected cervical tumor biopsies from 115 patients both before and 3 weeks into CRT. RNA-sequencing, Gene Set Enrichment Analysis and HPV gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…These results suggested that HPV oncogene expression is necessary not only in cervical cancer tumorigenesis but also in cervical cancer tumor progression through development of the mesenchymal transition, which has been associated with distant metastasis. These results also complement our recent research on local immune response and HPV expression in CRT (15). expression in CaSki positively correlated with the capacity to form spheroids (which is another mesenchymal feature) in vitro ( Figure 3D), while ME-180 with only CDH1 (E-cadherin) expression did not form spheroids ( Figure 3E).…”
Section: Resultssupporting
confidence: 88%
“…These results suggested that HPV oncogene expression is necessary not only in cervical cancer tumorigenesis but also in cervical cancer tumor progression through development of the mesenchymal transition, which has been associated with distant metastasis. These results also complement our recent research on local immune response and HPV expression in CRT (15). expression in CaSki positively correlated with the capacity to form spheroids (which is another mesenchymal feature) in vitro ( Figure 3D), while ME-180 with only CDH1 (E-cadherin) expression did not form spheroids ( Figure 3E).…”
Section: Resultssupporting
confidence: 88%
“…These technologies have been applied to investigate predictors and therapeutic targets of radiotherapy and chemotherapy resistance in many tumor types [ 5 7 ]. However, relatively few studies have examined CCRT resistance in CSCC [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such a rationale underscores the importance of earlier testing for HPV clearance. 26 Even with these questions and limitations in mind, our study is the first to show that PE of HPV within 6 weeks of definitive treatment with modern CRT portends a poor prognosis independently of other known prognostic markers such as posttherapy FDG-PET findings. Therefore, this 6-week window may represent a critical time point at which decisions could be made regarding treatment escalation.…”
Section: Cancer September 15 2020mentioning
confidence: 78%